1978
DOI: 10.3171/jns.1978.49.5.0711
|View full text |Cite
|
Sign up to set email alerts
|

Myelomeningocele before birth

Abstract: The authors report a study of 92 human embryos and four fetuses with myeloschisis. The characteristics of embryonic myeloschisis compared with spina bifida cystica in infants are: 1) the lesion is often more diffuse, involving the whole spinal cord (12 embryos); 2) the cervical cord is frequently affected (23 of the remaining 80 embryos); 3) holoprosencephaly is frequently associated (18 embryos); 4) meningocele is not found; and 5) hydrocephalus and Arnold-Chiari malformation are not yet developed. Hydrocepha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
46
0
2

Year Published

1981
1981
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(53 citation statements)
references
References 30 publications
5
46
0
2
Order By: Relevance
“…The debate about the best time to perform the MMC surgical repair reappeared alongside pathological observations, experimental models and initial experiences of intrauterine surgeries [2,21,22,23,24,25]. Since 1997, the number of experimental studies has been increasing and there is a growing body of clinical experience in fetal surgery in the United States [2, 6, 26].…”
Section: Discussionmentioning
confidence: 99%
“…The debate about the best time to perform the MMC surgical repair reappeared alongside pathological observations, experimental models and initial experiences of intrauterine surgeries [2,21,22,23,24,25]. Since 1997, the number of experimental studies has been increasing and there is a growing body of clinical experience in fetal surgery in the United States [2, 6, 26].…”
Section: Discussionmentioning
confidence: 99%
“…The rat fetus at 48 h of development is approximately equivalent to the human fetus at 24 days of development [3]. Osaka et al [7]have studied aborted myelodysplastic embryos and have concluded that the histology of the spinal cord at the level of dysplasia is relatively well preserved as late as the 55th day of gestation. Lendon’s studies [8]support the idea that the ‘dysplastic’ cord has relatively normal neuronal populations in many patients with myelomeningocele examined at autopsy.…”
Section: Discussionmentioning
confidence: 99%
“…There have been several reports supporting the idea that intrauterine repair of myeloschisis decreases the incidence of Chiari II malformations and shunt-dependent hydrocephalus in infants with spina bifida [12,13,14,15]. In contrast, others have reported complications with the mother or instances of symptomatic epidermoid inclusion cysts in the region of the conus [9,16].…”
Section: Discussionmentioning
confidence: 97%